Promising pyro-photo-electric catalysis in NaNbO3 via integrating solar and cold-hot alternation energy in pyroelectric-assisted photoelectrochemical system. (January 2021) - Zhang, Shaoce; Zhang, Bo; Chen, Dong; Guo, Zhengang; Ruan, Mengnan; Liu, Zhifeng
Abstract: Herein, a novel catalytic process named "pyro-photo-electric catalysis" is firstly realized by combining pyroelectric catalysis (PREC) and photoelectrochemical (PEC) catalysis based on NaNbO3 nanocubes. The films show enhanced photocurrent density of 0.37 mA/cm 2 at 1.23 V vs. a reversible hydrogen electrode (RHE) under 20–50 °C heating-cooling cycles and illumination, which is 3.1 and 1.6 times higher than that of PREC (0.09 mA/cm 2 ) and PEC catalysis (0.14 mA/cm 2 ). It is found that the higher catalysis efficiency can be the result of increased carrier concentration, including photogenerated carriers and pyro-generated carriers, and accelerated charge separation and transfer due to the change in band alignment at NaNbO3 /electrolyte caused by the imbalance of polarization charges and the induced pyroelectric potential. This study confirms the feasibility of pyroelectric-assisted PEC performance and realizes the energy harvesting of cold-hot alternation thermal energy and solar energy. It also provides insights into the rational design for designing new and ecofriendly photoelectrodes with efficient PEC water splitting. Highlights: The pyro-photo-electric catalysis combining pyroelectric and PEC catalysis based on NaNbO3 . The PEC performance of NaNbO3 is significantly improved upon the assist of pyroelectric effect. The pyroelectric effect generates pyro-generated carriers under cold-hot cycle. The induced pyroelectric potential accelerating charge separation and transfer. The pyroelectric-assisted PEC activity realizes the energy harvesting of thermal energy and solar energy.